ROLE OF GUIDANCE AND COUNSELLLING SERVICES ON NATIONAL INTEGRATION AMONG PRIMARY SCHOOL PUPILS IN NIGER STATE, NIGERIA (Journal of Guidance and Counselling Studies, 2023)
This paper examined the role of guidance and counselling services on national integration and enrolment among primary school pupils in Niger State, Nigeria. Two research questions were raised which among include what is the role of counselling service on national integration and enrolment among primary school pupils in Niger State? The study adopted descriptive survey design. The population of the study comprised of22,408 with 378 sample size. Multistage sampling technique was used. Twenty-three (23) self-designed structured-items questionnaire was used. Reliability of the instrument was ascertained through a test re-test method. The two sets of the results were correlated using Pearson Product Moment Correlation Coefficient (PPMC) aimed at finding consistency of the instrument and reliability coefficient of 0.92 was obtained which implies the instrument was reliable. Mean was used as statistical tool for data analysis. The study revealed that there are inadequate counselling human and material resources coupled with inadequate training and retraining of school guidance counsellors to promote guidance and counselling services in the schools. Also, effective guidance and counselling services will enhance national integration among pupils’ primary in the schools, there is inadequate facilities for guidance and counseling services in primary schools and effective counseling service will promote healthy school-community relationship among pupils in Niger State, Nigeria. It was recommended that the head-teachers should collaborate with School-Based Committee (SBMC) to provide adequate human and material resources with adequate training and retraining to promoteguidance and counselling services in the schools aimed at promoting national integration among pupils. Also, school guidance counsellor in collaboration with community through SBMC should establish healthy school-community relationship to promote positive national integration among pupils and in Niger State, Nigeria.
Keywords: Role; Guidance andCounselling Services; National Integration and Enrolment